Assessing the Indonesia-Vietnam Lobster Supply Chain Partnership through CBD Principles on Access and Benefit Sharing and Its Implications for the Sustainability of Kampung Lobster Teluk Jukung, West Nusa Tenggara - Adhitya Nini Rizki Apriliana; Ayu Riska Amalia; Lalu Guna Nugraha; Diva Pitaloka; Baiq Faridha Aulya Maharani (Fakultas Hukum Universitas Mataram, 2026)
Teluk Jukung in East Lombok has been designated as a national lobster aquaculture village, yet it continues to face structural challenges, including illegal lobster seed smuggling, limited technological capacity and inconsistencies in export regulations that place cultivators in a vulnerable economic and ecological position. In response, Indonesia has pursued a lobster supply chain partnership with Vietnam focused on technology transfer and fisheries downstream development. This cooperation raises legal and governance concerns regarding its compatibility with the Access and Benefit Sharing framework under the Convention on Biological Diversity, particularly the principles of Prior Informed Consent and Mutually Agreed Terms. This study adopts a socio-legal approach to examine the implementation of Access and Benefit Sharing within the Indonesia-Vietnam partnership and to assess its implications for ecosystem sustainability and the welfare of lobster cultivators in Teluk Jukung. The findings reveal three central issues. First, there is a persistent gap between national policy objectives and the socio-economic realities experienced by local cultivators. Second, shortcomings in the application of Prior Informed Consent and Mutually Agreed Terms contribute to unequal distribution of benefits within the supply chain. Third, an Access and Benefit Sharing-based governance model is required to ensure meaningful participation of cultivators, support equitable technology transfer and strengthen Indonesia’s position within the global lobster supply chain.This study offers policy recommendations aimed at developing a fair and sustainable framework for lobster aquaculture governance. Keywords: Teluk Jukung, Access and Benefit Sharing, Lobster Supply Chain, Lobster Seed